Kesenjangan Implementasi Undang-Undang Tindak Pidana Kekerasan Seksual: Analisis Empiris Perlindungan Hukum Bagi Pekerja Perempuan Korban Pelecehan Seksual di Tempat Kerja - Sendi Pratama Sugandi; Haidan Angga Kusumah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Workplace sexual harassment is a fundamental human rights violation that threatens the dignity of female workers. However, the implementation of Indonesia’s Sexual Violence Crime Act still reveals significant gaps between legal norms and practical realities. This study analyzes the implementation and barriers of legal protection for female workers experiencing workplace sexual harassment under the Sexual Violence Crime Act. Using a juridical-sociological approach with qualitative methods, data were collected through interviews with victims, investigators from the Women and Children Protection Unit of the Bandung Metropolitan Police, employers, HR managers, and victim advocates, supported by observation and document analysis of case files from 2023–2025. The findings indicate that most companies have not implemented sexual harassment prevention policies as required by Article 87 of the Act. Furthermore, limited case prosecution and secondary victimization remain major challenges for victims. Barriers are identified in three dimensions: legal substance, legal structure, and legal culture. This study highlights the need for implementing regulations, strengthening institutional capacity, and increasing legal awareness among employers and female workers to improve protection against workplace sexual harassment.